The Interplay Between Incoterms® and the CISG - Coetzee, Juana (Journal of Law and Commerce, 2013)
INCOTERMS® do not replace the CISG’s provisions on delivery and the passing of risk in toto, but merely supersede them in so far as they are mutually exclusive. For the rest, they function in tandem. Aspects which are not governed by the INCOTERMS® rules, or inadequately regulated, can be supplemented by the Convention, and vice versa. Collaboration between the two instruments strengthens the unified legal framework for international sales transactions with the view to facilitating international trade.